1999
DOI: 10.1046/j.1432-1327.1999.00420.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium‐binding properties and molecular organization of bradykinin

Abstract: The NMR features of bradykinin were investigated in dimethylsulfoxide containing 1% water. The temperature dependence of chemical shifts and ROESY maps were monitored for the major species where all X±Pro bonds are trans. The occurrence of a head-to-tail ionic interaction and intramolecular hydrogen bonds stabilizing a pseudo cyclic arrangement was inferred, a b turn at the C-terminus being the main feature of the secondary structure. Calcium was shown to bind to the peptide with a dissociation constant K d = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 31 publications
5
25
0
Order By: Relevance
“…Similar to AII, the conformation of BK in aqueous solution is considered to consist of an equilibrium between interconverting states, resulting from the peptide flexibility 67–70 . 13 C and 1 H NMR studies indicated that the trans configuration about the X‐Pro peptide bond is strongly favored 67.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to AII, the conformation of BK in aqueous solution is considered to consist of an equilibrium between interconverting states, resulting from the peptide flexibility 67–70 . 13 C and 1 H NMR studies indicated that the trans configuration about the X‐Pro peptide bond is strongly favored 67.…”
Section: Discussionmentioning
confidence: 99%
“…The dipolar aprotic solvent DMSO-d 6 was chosen because signals for labile protons such as those of the NH backbone protons, are often reduced or missing in aqueous media due to exchange with bulk water but readily observed in DMSO. Most peptides have good solubility in DMSO, and a large number of conformational studies of short peptides have been carried out in DMSO-d 6 (Oliva et al, 2000), including studies on Ca-binding peptides (Gaggelli et al, 1999). It is noteworthy that DMSO does not induce secondary structure (Yeagle et al, 2007), can act as an H-bond acceptor, but not a donor, and has a weaker tendency than water to co-ordinate to metal ions.…”
Section: Methodsmentioning
confidence: 99%
“…2,3 It plays many roles in pathophysiology, particularly as an initiator of inflammation. 4,5 This peptide exerts biological effects by binding to specific G-protein-coupled receptors 6 (B2) on the cell membrane, thereby triggering a series of poorly understood biochemical events that are manifested by pain, 7 contraction of smooth muscle, lowering of arterial pressure, 8 etc. Interactions of bradykinin with natural as well as artificial membranes are extensively investigated in order to elucidate the mechanism of the physiological activity of the peptide by several spectroscopic studies including CD, 9-11 13 C-and 1 H-NMR, [10][11][12] laser Raman spectroscopy, 13 and electron spin resonance spectroscopy, 14,15 The results suggested that the peptide's biological activity could be correlated with the extent of its interaction with the vesicles, supporting the hypothesis of an active role of the membrane as a catalyst for peptide-receptor interaction.…”
mentioning
confidence: 99%